Life cycle assessment of the coal-based synthetic natural gas plant in Ili, Xinjiang, China - Aite, Jarkhen Jumakhen (Jiaerkenjumaken); Annachhatre, Ajit P.; Shipin, Oleg V.; Bohez, Erik L.J.; International Fellowship Program; Ford Foundation, USA; Asian Institute of Technology Fellowship (Pathum Thani : Asian Institute of Technology, 2013)
With tremendous growth of economy and relative limited resources, energy demand is at a critical level in China. Under the pressure of needing energy for the rapid growth of economy, and because of the abundant energy resources in West China, the central government set a Great Western Development Strategy in 2001 to develop the energy industries in western China. Based on this, Ili Key Nation Coal Chemical Industry Base approved by the Central Government was established in Ili Kazakh Autonomous Prefecture of Xinjiang, China in 2007, which plans to produce 30 billion mp3 (Bof natural gas and billions of tons of chemical products annually and has attracted numerous large enterprises to the area. However, the most profound problem in the coal-based chemical plant which is high water consumption, it could aggravate lack of water resources in arid with coal-rich region since 1 ton of methanol producing from coal needs around 20 mp3 (Bof fresh water and huge amount of wastewater to be discharged (2008 as cited in Yang et al. 2012), and it takes 10 to 12 mp3 (Bof water to produce a metric ton of fuel (Schneider, 2011). Furthermore, coal mining itself is a high water-depleted enterprise (Qiu 2010 as cited in Yang et al 2012). With the input of tremendous coal, water, energy and chemicals in Coal-based synthetic natural gas (SNG) plants are and a complex high-tech in its entire life cycle, the output is more compound and unthinkable. As LCA focus on accumulative environmental impact during whole life of the products, and SimaPro is considered the most widely used in world for LCA software, so the LCA via SimaPro are taken to the research. The study presents the results of environmental impact of coal-based SNG with eco-indicator 99 (H/A), and its impact in human health, ecosystem and resources are discussed. Its boundary with coal mining, coal transportation, gasification/methanationis attentive reviewed with the function unit (FU) of 1 mp3 (Bof SNG in 2nd order LCA. The coal-based SNG plant configurations include coal crushing, gasifier, gas cooling, shift convention, Rectisol Unit and gasification/methanation. The comparison of cleanness in energy consumption of coal with SNG and in generation of electricity and steam in thermal power station with NG cogeneration plant based on damage effect and heating value associated with each project. s
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Environmental Engineering and Management
Thesis (M.Eng.) - Asian Institute of Technology, 2013
Keywords: Coal gasification -- China -- Xinjiang; Natural gas -- China -- Xinjiang